Reaction of Ascorbic Acid with Aliphatic Amines - Pischetsrieder, Monika; Larisch, Bernd; Müller, Ursula; Severin, Theodor (Journal of Agricultural and Food Chemistry, 1995)
Ascorbic acid (1) reacts with propylamine or α-N-acetyllysine to afford N-substituted 3-deoxy-3-aminoascorbic acid of general structure 3.
UnivIS-Import:2015-03-05:Pub.1995.nat.dchph.llmch.reacti
Keywords: Aliphatic amines; Aminoreductones; Ascorbic acid